Assessment of normal tricuspid valve anatomy in adults by real-time three-dimensional echocardiography - Anwar, Ashraf M. (Springer Netherlands, 2007)
BACKGROUND: The tricuspid valve (TV) is a complex structure. Unlike the aortic and mitral valve it is not possible to visualize all TV leaflets simultaneously in one cross-sectional view by standard two-dimensional echocardiography (2DE) either transthoracic or transesophageal due to the position of TV in the far field. AIM: Quantitative and qualitative assessment of the normal TV using real-time 3-dimensional echocardiography (RT3DE). METHODS: RT3DE was performed for 100 normal adults (mean age 30 ± 9 years, 65% males). RT3DE visualization was evaluated by 4-point score (1: not visualized, 2: inadequate, 3: sufficient, and 4: excellent). Measurements included TV annulus diameters (TAD), TV area (TVA), and commissural width. RESULTS: In 90% of patients with good 2DE image quality, it was possible to analyse TV anatomy by RT3DE. A detailed anatomical structure including unique description and measurement of tricuspid annulus shape and size, TV leaflets shape, and mobility, and TV commissural width were obtained in majority of patients. Identification of each TV leaflet as seen in the routine 2DE views was obtained. CONCLUSION: RT3DE of the TV is feasible in a large number of patients. RT3DE may add to functional 2DE data in description of TV anatomy and providing highly reproducible and actual reality (anatomical and functional) measurements.